Signifikansi: Proses Pencarian Makna Terhadap Teks-teks Agama (Menyibak Pemikiran Nasr Hamid Abu Zaid) - Muzakki, Akhmad (ULUL ALBAB Jurnal Studi Islam, 2004)
Naturally, said Gadamer, word belongs to and is taken from reality. Human being looks for appropriate words as form of expression for reality. Ontologically, language created by human being is not only as a means of communication and thinking, but rather it is seen as the manifestation of reality, while they are articulating that language. Therefore, the meaning of a word is in the concept of thought. In the linguisticÂ theory of Saussure, a word is a sign related to signifiant (which gives meaning) and signifie (which is given meaning). The signifiant gives form or expression while signifie concept or meaning. The relationship between the signifiant and the signifie based on the social convention is called signification, or "maghza" in Nasr Hamid's term. In other words, the signification is the effort of giving the meaning to the sign (language). Among the language philosophers, Jacques Derrida, for instance, the last signifie is not always admitted. Derrida said, meaning appears due to metaphor exchange and meaning changes when the speakers change. Or, as what Nasr Hamid had expressed, the meaning of the religious texts are not established when the text was made, but rather it is dynamic, relational, and changing depending on the socio-historical background of the readers.Â